2016
DOI: 10.1158/1078-0432.ccr-15-2260
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Histone Deacetylase Inhibitor Treatment Leads to Tumor Growth Arrest and Multi-Lineage Differentiation of Malignant Rhabdoid Tumors

Abstract: Purpose: Malignant rhabdoid tumor (MRT) and atypical teratoid rhabdoid tumors (ATRT) are rare aggressive undifferentiated tumors primarily affecting the kidney and CNS of infants and young children. MRT are almost exclusively characterized by homozygous deletion or inactivation of the chromatin remodeling gene SMARCB1. SMARCB1 protein loss leads to direct impairment of chromatin remodeling and we have previously reported a role for this protein in histone acetylation. This provided the rationale for investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 33 publications
3
33
0
Order By: Relevance
“…A characteristic feature of HDACi in many tumor and cell types is the induction of a more differentiated phenotype (48,49). Since a recent study demonstrated that membranous CD24 expression was correlated with a more differentiated phenotype in PDAC (50), we examined the effects of 4SC-202 treatment on CD24 expression.…”
Section: Resultsmentioning
confidence: 99%
“…A characteristic feature of HDACi in many tumor and cell types is the induction of a more differentiated phenotype (48,49). Since a recent study demonstrated that membranous CD24 expression was correlated with a more differentiated phenotype in PDAC (50), we examined the effects of 4SC-202 treatment on CD24 expression.…”
Section: Resultsmentioning
confidence: 99%
“…In most cases, the tumours recurred locally and the majority of patients ultimately developed metastatic disease [3,4,6]. Future treatments with agents that target the epigenetic machinery such as inhibitors against Enhancer of Zeste homologue 2 (EZH2) or histone deactylase may prove even more effective [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…While some authors consider SASP to be the “dark” side of senescence [91,92,93,94,95,96], others have proposed that induction of senescence (SIPS) might be advantageous for cancer treatment [97,98,99,100,101]. As pointed out by Maier et al [101], although “ accumulation of senescent cancer cells leads to an increased secretion of inflammatory cytokines, which might cause age-related pathologies, like secondary cancers, in the long term, the primary aim of cancer treatment leading to a longer overall survival should always take preference.…”
Section: Activation Of Apoptotic Signaling Does Not Always Lead Tomentioning
confidence: 99%
“…Other studies, however, also reporting extensive experimental and clinical data, have concluded that this response might reflect a favorable therapeutic outcome (e.g., [131]). Similarly, the conclusions that SIPS might represent a favorable [97,98,99,100,101] or unfavorable [97,98,99,100,101,102,103] therapeutic outcomes have also been based on extensive experimental/clinical data. Such apparently conflicting observations might not be entirely unexpected when considering the distinct mutational types in aging and cancer.…”
Section: Mutational Signatures In Human Cancersmentioning
confidence: 99%